1994
DOI: 10.1016/0014-5793(94)80278-5
|View full text |Cite
|
Sign up to set email alerts
|

Sequence similarity of mammalian epoxide hydrolases to the bacterial haloalkane dehalogenase and other related proteins

Abstract: Direct comparison of the ammo acid sequences of mlcrosomal and soluble epoxlde hydrolase superficially mdlcates that these enzymes are unrelated Both protems, however, share slgmficant sequence slmllanty to a bacterial haloalkane dehalogenase that has earlier been shown to belong to the a@ hydrolase fold family of enzymes The catalytic mechanism for the dehalogenase has been elucidated m detail [Verschueren et al (1993) Nature 363, 693-6981 and proceeds via an ester mtermedlate where the substrate IS covalentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
138
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 30 publications
0
138
0
Order By: Relevance
“…This enzyme, which represents a single known and highly conserved gene product with over 90% homology between rodent and human (30), can be inhibited selectively and competitively in vitro by a variety of urea, carbamate, and amide derivatives (16,18). We have shown that injection of one such inhibitor, DCU, into spontaneously hypertensive rats resulted in a lowering of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme, which represents a single known and highly conserved gene product with over 90% homology between rodent and human (30), can be inhibited selectively and competitively in vitro by a variety of urea, carbamate, and amide derivatives (16,18). We have shown that injection of one such inhibitor, DCU, into spontaneously hypertensive rats resulted in a lowering of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…This information has been forthcoming from numerous sequence comparisons, biochemical, and crystallographic investigations. Based on sequence alignment analyses, it was concluded that sEH belongs to a broad group of a/b hydrolase enzymes that include bacterial haloalkane dehalogenase [32,66]. The alignment characterization also lead to identification of a proposed catalytic triad of amino acids within sEH.…”
Section: Mechanism Of Action/enzymatic Mechanismmentioning
confidence: 99%
“…Like sEH, mEH is a member of the a/b-hydrolase enzyme family [66]. Based on its similarity with bacterial haloalkane dehalogenases and other epoxide hydrolases, a catalytic triad consisting of a His 431 , Asp 226 , and a Glu 404 has been proposed [129,130].…”
Section: Mechanism Of Action/enzymatic Mechanismmentioning
confidence: 99%
“…The soluble epoxide hydrolase (sEH, EC 3.3.2.3) 1 is a member of the α/β-hydrolase fold family of enzymes [1] and catalyzes the hydrolysis of an epoxide to its corresponding diol through the catalytic addition of a water molecule [2]. The endogenous substrates for the sEH include epoxides of arachidonic acid [3,4] and linoleic acid [5,6].…”
Section: Introductionmentioning
confidence: 99%